Developing indicators of risk to environmental variability based on species dependency in U.S. fishing communities in the Northeast and Southeast Regions - Tarsila Seara; Matthew McPherson; Patricia M. Clay; Michael Jepson; Lisa L. Colburn; Changhua Weng; Angela Silva (PLoS ONE, 2025)
Fishing communities worldwide have or are likely to experience social, economic, and cultural impacts from environmental variability. Changes in marine fisheries will require adaptation by fishing communities and fisheries managers alike. Here, Community Environmental Variability Risk Indicators (CEVRI) were developed to assess risk to environmental change for fishing communities in the U.S. Northeast and Southeast Regions based on spatial and temporal trends between 2000 and 2022. To accomplish this, we analyzed commercial landings value as it relates to species level Climate Vulnerability Assessment (CVA) scores for species considered commercially, recreationally, and ecologically important. The CVA considers the vulnerability of species to 12 sensitivity and 12 exposure factors relating to important environmental factors within the regional context. Here, we used three sensitivity factors: Stock Size/Status, Ocean Acidification, and Temperature, as well as Total Sensitivity and Total Vulnerability. Community level scores were used to analyze intra and inter region variation, and to understand trends in community risk as revenue dependence on different species changes through time. In general, communities in the Gulf of America/Florida Keys sub-region presented lower risk to the factors analyzed than the South Atlantic sub-region and the Northeast. Ocean Acidification was the sensitivity factor with the highest levels of risk for communities. The findings of this study have important applications to inform decision-making and to help communicate environmental variability associated risks to broader audiences, thus further developing the ability of stakeholders to understand and assess cumulative impacts and complex trade-offs affecting the sustainability of marine ecosystems and resources.